Regulation of ERα Stability and Estrogen Signaling in Breast Cancer by HOIL-1 - Ding, Jianing; Kuang, Peng (Frontiers in Oncology, 2021)
Estrogen receptor α (ERα) is the major driver for breast tumor carcinogenesis and progression, while ERα positive breast cancer is the major subtype in breast malignancies, which account for 70% breast cancers in patients. The success of endocrine therapy such as tamoxifen is one of the biggest breakthroughs in breast cancer treatments. However, the endocrine therapy resistance is a headache problem in breast cancer. Further mechanisms need to be identified to the effect of ERα signaling in controlling breast cancer progression and drug resistance. HOIL-1 was firstly identified as the ERα transcriptional co-activator in modulating estrogen signaling in breast cancer. In our current study, we showed that HOIL-1, which was elevated in breast cancer, related to good prognosis in ERα positive breast cancer, but correlated with poor outcome in endocrine-treated patients. HOIL-1 was required for ERα positive breast cancer proliferation and clone formation, which effect could be rescued by further ERα overexpression. Further mechanism studies showed that HOIL-1 is required for ERα signaling activity in breast cancer cells. HOIL-1 could interact with ERα in the cytosol and modulate ERα stability via inhibiting ERα K48-linked poly-ubiquitination. Thus, our study demonstrated a novel post-translational modification in ERα signaling, which could provide novel strategy for ERα-driven breast cancer therapy.